UPAYA MENINGKATKAN KETERAMPILAN MENULIS PANTUN DENGAN MODEL PEMBELAJARAN KONTEKSTUAL PADA PESERTA DIDIK KELAS V SD - Muspirati Muspirati (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The purpose of this research is to improve the skill of writing rhymes. The subjects in this study were educators and fifth grade students of SD Negeri 01 Pasangkayu. The teaching methods and methods tend to be conventional and traditional, thus making the students' ability to write poems lacking. Contextual learning model is one of the efforts used to improve the ability to write rhymes. This classroom action research (CAR) was carried out in two cycles. Starting with the identification of problems that exist in the classroom by taking pre-cycle actions. The stage of each cycle begins with planning in the form of compiling learning steps through the application of contextual models. The results showed that the application of the contextual model had improved the students' skills in writing rhymes. The skills of educators in this study have been declared complete. The skills of students in learning have increased from cycle one and cycle two, in cycle one educators achieved a good category with a success percentage of 77% and in cycle II increased by 96% with a very good category. The activities of students have reached the indicators of success and are declared complete. The activity of students in learning has increased, in cycle one it reaches a good category. In the aspect of student attention, it was 85%, in the second cycle it increased by 95%. In the aspect of the learning situation of students in the first cycle of m80%, and in the second cycle of 85%. The children's poetry writing skills have reached the indicators of success and were declared complete. Classical learning completeness in the pre-cycle is only 35%, and in the first cycle it increases by 80%, and in the second cycle the increase reaches 100%. This research is proven to be able to improve the quality of learning which includes the skills of educators, student activities and the results of rhyme writing skills.